You should know that multiplying and dividing the given expression by the same amount, you will get an equivalent expression.

Multiplying and dividing the given expression by `x + 4` yields:

`(x - 4) = ((x - 4)(x + 4))/(x + 4)`

You should notice that reducing the duplicate factors, the expression becomes equal to the original one.

Converting the product from numerator into a difference of squares, yields:

`(x - 4) = (x^2 - 4^2)/(x + 4) => (x - 4) = (x^2 - 16)/(x + 4)`

You should notice that the number of equivalent expressions that could be generated is infinite.

**Hence, evaluating one equivalent expression to the given x - 4, yields **`(x - 4) = (x^2 - 16)/(x + 4).`